(untitled) - Tuchman, Barbara W. (London, 1984)
Pulitzer Prize–winning historian Barbara W. Tuchman, author of the World War I masterpiece The Guns of August, grapples with her boldest subject: the pervasive presence, through the ages, of failure, mismanagement, and delusion in government.
Keywords: Lịch sử, hiện đại,History, modern